Whether we have free-will and whether it matters - Ostrowick, John Montague (My University, 2007)
There is a concern that causal determinism might render free-will impossible. I compare some different perspectives, namely Compatibilism, Incompatibilism, Libertarianism, and Hard Determinism, and conclude that Hard Determinism is correct—we lack free-will. To further bolster the case, I consider the work of Libet, who has found neuropsychological evidence that our brains non-consciously cause our actions, prior to our being aware of it. Thus we are also not choosing consciously. I then consider Dennett’s work on the role of the conscious self. I defend his model—of a fragmented self—which could not cause our actions. Finally I argue that many things that free-will purportedly provides, eg., justification for the penal system and reactive attitudes, can be reconstructed without free-will. I then end with some speculations about why people still want free-will.
Student Number : 9112588A - MA Dissertation - School of Social Sciences - Faculty of Humanities
Keywords: Compatibilism; Incompatibilism; Libertarianism; Hard Determinism; Free-will; the Self; Libet; Dennett; Reactive Attitudes; Penal system